Robust Macroscopic 3D Sponges of Manganese Oxide Molecular Sieves. Issue 64 (18th September 2017) - Liu, Zhenxin; Wu, Depeng; Guo, Xuehui; Fang, Shaoming; Wang, Lizhen; Xing, Yu; Suib, Steven L.
Abstract: The construction of macroscopic 3D sponges is of great technological importance for various applications. An outstanding challenge is the facile fabrication of sponges with the desirable combination of good stability, high electrical conductivity, and absorption ability. Here free‐standing 3D OMS‐2 sponges are demonstrated, with various densities, which possess a combination of desirable physical properties including high porosity, robustness, permeability, recyclability, high electrical conductivity, and selective water absorption in preference to oil. Some of these properties have systematic trends with various densities. The stress of the OMS‐2 sponge, made by nanowire‐based freeze‐drying process, is four orders of magnitude higher than that made by calcination‐related process. These new materials should find practical applications in environmental, catalysis, sensing, absorption, and energy storage, particularly in the removal of water spill cleanup, and beyond. Abstract : Suck it up : Free‐standing 3D OMS‐2 sponges with various densities were developed and demonstrated outstanding features, including good mechanical properties, facile preparation, high electrical conductivity, high porosity, permeability, recyclability, as well as selective water absorption in preference to oil. Some of these properties exhibit systematic trends with various densities.